Implementation of the Discrete Cosine Transform (DCT) Steganography Method for Embedding Secret Messages in Image Media - Amsal Tampubolon; Michael Ginting; Eunike Charina I. Tarigan (Sean Institute, 2026)
Steganography is a technique for hiding secret information within a cover medium so that the existence of the message is not easily detected. One of the steganography methods widely used in image media is the Discrete Cosine Transform (DCT), which works by transforming an image into the frequency domain before message embedding is performed. This study aims to implement a DCT-based steganography method for embedding secret messages into image media and to analyze the quality of the resulting stego images. The embedding process is carried out by modifying DCT coefficients in certain image blocks so that the resulting changes are not visually noticeable. The experimental results show that the DCT method is able to embed secret messages into images with a low level of distortion while maintaining visual quality. Thus, the DCT steganography method is proven to be effective as one of the image-based information security techniques.